PERCEIVED CORPORATE CREDIBILITY, SERVICE QUALITY, KNOWLEDGE AND SELF-EFFICACY WITH BUSINESS ZAKAT COMPLIANCE - Siti Maziah Ab Rahman; Maheran Zakaria; Rustam Shaari; Noreen Azella Nawi; Nurul Ainaa Mohd Zain (Journal of Islamic, Social, Economics and Development, 2019)
The purpose of this research is to investigate the expectancy theory with zakat compliance action among firms in Kelantan. A study in Kelantan is a matter of how many companies in Kelantan know and are aware of business zakat. The questionnaire was distributed to respondents living in Kelantan, the public sector and the private sector from companies listed in zakat paying under the Islamic Religious & Customs Ceremony in Kelantan. The questionnaire was formed into six parts, one consisting of respondents’ demographic information and other parts related to zakat compliance by firms. Researchers have issued four independent variables that are considered perceived corporate credibility, service quality, knowledge and self- efficacy towards zakat compliance action among business by firms. From the analysis of the findings, it can be concluded that the key factor that determines the corporate zakat compliance behaviour is the service quality, knowledge and self-efficacy.